Retroviral hijacking of host transport pathways for genome nuclear export - Ryan T. Behrens; Nathan M. Sherer (mBio, 2023)
ABSTRACTRecent advances in the study of virus-cell interactions have improved our understanding of how viruses that replicate their genomes in the nucleus (e.g., retroviruses, hepadnaviruses, herpesviruses, and a subset of RNA viruses) hijack cellular pathways to export these genomes to the cytoplasm where they access virion egress pathways. These findings shed light on novel aspects of viral life cycles relevant to the development of new antiviral strategies and can yield new tractable, virus-based tools for exposing additional secrets of the cell. The goal of this review is to summarize defined and emerging modes of virus-host interactions that drive the transit of viral genomes out of the nucleus across the nuclear envelope barrier, with an emphasis on retroviruses that are most extensively studied. In this context, we prioritize discussion of recent progress in understanding the trafficking and function of the human immunodeficiency virus type 1 Rev protein, exemplifying a relatively refined example of stepwise, cooperativity-driven viral subversion of multi-subunit host transport receptor complexes.